2019
DOI: 10.1002/ece3.5764
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of suburban juvenile European hedgehogs (Erinaceus europaeus) in Denmark

Abstract: European hedgehog (Erinaceus europaeus) populations are widespread across diverse habitats but are declining in Western Europe. Drastic declines have been described in the UK, with the most severe declines occurring in rural areas. Hedgehogs are widely distributed in Denmark, but their status remains unknown. Fieldwork on hedgehogs has tended to focus on rural areas, leaving their ecology in suburban habitats largely unexplored, with clear implications for conservation initiatives. Here, we study the ecology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(101 citation statements)
references
References 37 publications
4
96
1
Order By: Relevance
“…Thus, these numbers from rural areas, when combined with the numbers of decline from our urban study, suggest that hedgehogs are declining in general. On the other hand, a recent study found high juvenile survival rates in a suburban area, pointing towards healthy populations in this habitat [23]. Therefore, our observed population decline might be caused by factors that are patchily distributed and which are not acting on all populations.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Thus, these numbers from rural areas, when combined with the numbers of decline from our urban study, suggest that hedgehogs are declining in general. On the other hand, a recent study found high juvenile survival rates in a suburban area, pointing towards healthy populations in this habitat [23]. Therefore, our observed population decline might be caused by factors that are patchily distributed and which are not acting on all populations.…”
Section: Discussionmentioning
confidence: 51%
“…These estimates were obtained by using the relative return rate of the survey cards (for 1992), and the hedgehog level from the footprint tunnels (for 2016-2018) in combination with the CMR numbers from the respective year. In addition, the km-squares were divided in three abundance categories of low (0-19 hedgehogs per km 2 ), medium (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and high (>40) and their frequency in each survey was plotted.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas we found a similar mean monthly survival rate of 64% for juveniles and subadults over nine months, our figure for adults was much higher at 85%. Rasmussen et al 2019 [51] found a slightly higher juvenile survival rate of 70% over one year, with an over winter survival rate of 89%, they attribute this high winter survival to the suburban habitat type.…”
Section: Comparison With Other Hedgehog Speciesmentioning
confidence: 97%
“…It is triggered primarily by consistently low temperatures (<8 • C) [7], although photoperiod, body-condition and food availability may also be involved [8]. Date and duration of hibernation periods can be influenced by climate, individual condition and sex [7][8][9].…”
Section: Hibernationmentioning
confidence: 99%